Mindful Eating and Its Link with Dietary Intake and Obesity Risk among Adults and Older Adults: A Scoping Review - Fauziyyah, Hana; Zainuddin, NurZetty Sofia; Vanoh, Divya; Ahmad, Affizal; Draman, Nani; Hazizi, Aqilah Hadhirah (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
The current review aimed to map the available evidence on the assessments of mindful eating and dietary intake, and the relationship between mindful eating level, food group intake, nutrient intake, and obesity risk. This scoping review is based on Preferred Reporting Items for the Systematic Review and Meta-Analyses Extension for the Scoping Review (PRISMA-ScR) and the Joanna Briggs Institute (JBI) 2020 framework. A literature search was conducted on Web of Science, PubMed, and ScienceDirect databases for studies published between 2014 to 2024, identifying eligible primary studies involving adult and elderly participants. Twenty-two studies were chosen for this review. Most studies assessed mindful eating using Mindful Eating Questionnaire (MEQ), Five-Facet Mindfulness Questionnaire, and Mindful Attention Awareness Scale (MAAS). Mindful eating practice was associated with lower snack consumption, and specific sub-scales showed a favorable correlation (p<0.05) with fruit and vegetable intake. Body Mass Index (BMI) reductions were observed in the intervention group (MD 0.51, p<0.001). This scoping review demonstrates the scientific basis of the mindful eating promote increased consumption of nutritious foods and nutrients, which is likely to lead to a reduction in obesity risk.